Hydrogen storage alloy for alkaline storage battery
Patent Information
- Application Number
- JP2023122351
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
【0033】 本発明のアルカリ蓄電池用水素吸蔵合金は、電池の低コスト化をもたらすとともに、この水素吸蔵合金を用いたアルカリ蓄電池は、高出力密度を有し、特に優れた充放電サイクル寿命特性(耐久性)も優れているため、放電容量特性に優れる。このため、本発明に係るアルカリ蓄電池用水素吸蔵合金は、各種用途、特に車載の使用条件でも十分に高い高率放電ができるアルカリ蓄電池に用いることができる。
Smart Images

Figure 2025018552000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogen storage alloy for use in an alkaline storage battery. [Background technology]
[0002] Nickel-metal hydride secondary batteries have a higher capacity than nickel-cadmium batteries and do not contain any environmentally hazardous substances. For this reason, nickel-metal hydride secondary batteries have come to be used in a wide range of applications in recent years, from mobile phones and personal computers, power tools, and consumer applications as a replacement for alkaline primary batteries to hybrid electric vehicles (HEVs). Alkaline storage batteries are primarily used for these applications.
[0003] Conventionally, hydrogen storage alloys with an AB5 crystal structure have been used for the negative electrodes of alkaline storage batteries, but this alloy has limitations in terms of reducing the size and weight of batteries, and there has been a demand for the development of new hydrogen storage alloys that can achieve a small size and high capacity. As a solution to this problem, Patent Documents 1 and 2 propose rare earth-Mg transition metal hydrogen storage alloys that contain Mg.
[0004] In addition, as a method for reducing the size and weight of an alkaline storage battery, for example, it is possible to reduce the amount of hydrogen storage alloy used in the negative electrode of the alkaline storage battery. However, reducing the amount of hydrogen storage alloy causes new problems such as a decrease in discharge capacity or a decrease in output due to a decrease in nickel active sites. To solve this problem, Patent Document 3 proposes a method of increasing the operating voltage by using a hydrogen storage alloy with a high hydrogen equilibrium pressure.
[0005] In addition, some rare earth-Mg-Ni based alloys have been proposed as hydrogen storage alloys. For example, Patent Document 4 proposes a hydrogen storage alloy having excellent corrosion resistance and durability, and a nickel-metal hydride storage battery using the hydrogen storage alloy having excellent cycle life characteristics. 1-a-b Sm a Mg b )(Ni 1-c-d Al c M d )x A hydrogen storage alloy represented by (0.1 ≦ a ≦ 0.25; 0.1 < b < 0.2; 0.02 < cx < 0.2; 0 ≦ dx ≦ 0.1; 3.6 ≦ x ≦ 3.7; RE is one or more elements selected from rare earth elements other than Sm and Y; La is essential, and M is Mn and / or Co) is disclosed.
[0006] Also, Patent Document 5 reports providing an alkaline storage battery that is inexpensive, has good discharge output characteristics, and excellent high-temperature durability. As one embodiment of the invention described in Patent Document 5, in the hydrogen storage alloy negative electrode, a general formula (La x Ln y ) 1-z Mg z Ni t-u T u (T is selected from Al, Co, Mn, Zn, Ln is at least one selected from rare earth elements other than La and Y, x > y, 0.09 ≦ z ≦ 0.14, 3.65 ≦ t ≦ 3.80, 0.05 ≦ u ≦ 0.25), having a hexagonal (2H) A5B 19 type crystal structure, a trigonal (3R) A5B 19 type crystal structure, and an A2B7 type crystal structure, and using a powder X-ray diffraction intensity peak by Cu-Kα line of the hexagonal (2H) A5B 19 type crystal structure that is larger than those of the trigonal (3R) A5B 19 type crystal structure and the A2B7 type crystal structure.
[0007] Patent Document 6 discloses a hydrogen storage alloy in which inexpensive Fe is used to reduce the cost, improve the corrosion resistance, and enhance the charge acceptance of a rare earth-magnesium-nickel-based hydrogen storage alloy. Specifically, a general formula (La a Nd b A c B d ) l-v Mg v Ni w Al x Fe y T z(A is at least one element selected from Sm and Gd, B is at least one element selected from Pr, Eu, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, Zr, Hf, Ca, and Y, and T is at least one element selected from V, Nb, Ta, Cr, Mo, Mn, Co, Ga, Zn, Sn, In, Cu, Si, P, and B), and a, b, c, and d in the general formula have the relationships of 0 ≦ a, 0 ≦ b, 0 ≦ c, 0 ≦ d < 0.1, a + b + c + d = 1, and 0 ≦ z ≦ 0.5. Also, the molar ratio v of Mg in the general formula is 0.10 ≦ v ≦ 0.25, the molar ratio x of Al is 0.10 ≦ x ≦ 0.20, the molar ratio y of Fe is 0.05 ≦ y ≦ 0.15, and a hydrogen storage alloy satisfying 3.45 ≦ w + x + y + z ≦ 3.65 has been reported.
[0008] Patent Document 7 discloses a hydrogen storage alloy for use in an alkaline storage battery. The hydrogen storage alloy has, as the main phase, one or two crystal structures selected from the A2B7-type crystal structure and the AB3-type crystal structure, and has the general formula (La 1-a-b Ce a Sm b ) 1-c Mg c Ni d Al e Cr f Here, the subscripts a, b, c, d, e, and f in the formula satisfy the conditions of 0 < a ≦ 0.15, 0 ≦ b ≦ 0.15, 0.17 ≦ c ≦ 0.32, 0.02 ≦ e ≦ 0.10, 0 ≦ f ≦ 0.05, and 2.95 ≦ d + e + f < 3.50.
[0009] On the other hand, Non-Patent Document 1 has a chapter on the influence of Ce on RE-Mg-Ni-based hydrogen storage alloys (RE: rare earth element). Specifically, Non-Patent Document 1 discloses, as RE-Mg-Ni-based hydrogen storage alloys, (La 0.5 Nd 0.5 ) 0.85 Mg 0.15 Ni 3.3 Al 0.2 , (La 0.45 Nd 0.45 Ce 0.1 ) 0.85 Mg 0.15 Ni 3.3 Al0.2 , (La 0.4 Nd 0.4 Ce 0.2 ) 0.85 Mg 0.15 Ni 3.3 Al 0.2 , (La 0.3 Nd 0.3 Ce 0.4 ) 0.85 Mg 0.15 Ni 3.3 Al 0.2 Alloys are disclosed and the results of evaluating these alloys are reported.
[0010] Non-Patent Documents 2 and 3 state that Mm 0.83 Mg 0.17 Ni 2.94-x Al 0.17 Co 0.2 Fe x A hydrogen storage alloy represented by (0≦x≦0.2) has been reported.
[0011] Non-patent literature 4 states that 0.7 Mg 0.3 Co 0.45 Ni 2.55-x Fe x A hydrogen storage alloy represented by the following formula has been reported.
[0012] Non-patent literature 5 states that 0.80 Mg 0.20 Ni 2.85 Al 0.11 M 0.53 Hydrogen storage alloys represented by (M=Ni, Si, Cr, Cu, Fe) have been reported.
[0013] In Non-Patent Document 6, La2Ni 6.9-x Al 0.1 Fe x The properties of hydrogen storage alloys expressed as (0≦x≦2.1) have been reported. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] Japanese Patent Application Publication No. 11-323469 [Patent Document 2] WO 01 / 48841 [Patent Document 3] JP 2005-32573 A [Patent Document 4] JP 2016-69692 A [Patent Document 5] JP 2014-229593 A [Patent Document 6] JP 2011-14258 A [Patent Document 7] International Publication No. 2021 / 205749 [Non-patent literature]
[0015] [Non-Patent Document 1] Shigekazu Yasuoka, PhD thesis: Practical application of rare earth-Mg-Ni (superlattice) hydrogen storage alloys and development of high-performance commercial nickel-metal hydride batteries using them (2017, Kyoto University) [Non-Patent Document 2] Tiejun Meng et al., Batteries 2,(2016)34 [Non-Patent Document 3] Tiejun Meng et al., Batteries 3,(2017)28 [Non-Patent Document 4] Yang-huan Zhang et al.,Materials Charactarization 61(2010)305 [Non-Patent Document 5] XU Guochang et al., J. Rare Earth 27 (2009) 250 [Non-Patent Document 6] Hideaki Sodeyama et al.: Proceedings of the Ibaraki Conference p.137 (co-hosted by the Kanto Branch of the Japan Society of Mechanical Engineers and the Japan Society of Precision Engineering, published on September 28, 2007) Summary of the Invention [Problem to be solved by the invention]
[0016] However, the techniques disclosed in Patent Documents 1 and 2 above have not been put to practical use in various applications because the alloys have not been optimized.
[0017] Furthermore, in the technique disclosed in Patent Document 3, when a hydrogen storage alloy with a high hydrogen equilibrium pressure is used, a new problem occurs in that the cycle life characteristics are reduced.
[0018] Although the hydrogen storage alloy disclosed in Patent Document 4 has improved cycle characteristics, further improvements, including improvements in discharge capacity and, in particular, rate characteristics, are required for practical use.
[0019] In addition, the technology disclosed in Patent Document 5 shows the appropriate crystal phase structure by X-ray diffraction intensity, but the hydrogen equilibrium pressure (defined as the dissociation pressure when the hydrogen storage capacity (H / M) at 40°C is 0.5) is too high, which may cause problems when used as a battery.
[0020] In addition, although the technology disclosed in Patent Document 6 is characterized by the use of inexpensive Fe, it was based on an alloy containing expensive Nd, and as a result, it was not possible to achieve low cost, and further improvement in durability was required.
[0021] Furthermore, the technology disclosed in Patent Document 7 is characterized by an inexpensive hydrogen storage alloy for alkaline storage batteries, but there has been a demand for an alloy that is even cheaper and has higher durability.
[0022] On the other hand, Non-Patent Document 1 concludes that rare earth-Mg-Ni alloys containing Ce have a low hydrogen absorption / release capacity and are prone to pulverization when hydrogen absorption / release is repeated, and therefore it has become clear that such alloys are subject to significant degradation when used as electrodes for nickel-metal hydride batteries.
[0023] In addition, Non-Patent Documents 2 and 3, Mm 0.83 Mg 0.17 Ni 2.94-x Al 0.17 Co 0.2 Fe xFor (0≦x≦0.2), material properties and battery properties have been reported. However, the hydrogen storage alloys disclosed in Non-Patent Documents 2 and 3 have cycle properties that are insufficient for practical use, and since they contain Co, they are not inexpensive alloys. Therefore, there was a need to achieve both lower cost and higher durability.
[0024] In addition, Non-Patent Document 4 states that 0.7 Mg 0.3 Co 0.45 Ni 2.55-x Fe x Although the characteristics of (0≦x≦0.4) have been disclosed, the cycle characteristics are insufficient and further improvement of the characteristics is required for practical use.
[0025] In addition, La 0.80 Mg 0.20 Ni 2.85 Al 0.11 M 0.53 In the case of (M=Ni, Si, Cr, Cu, Fe) alloys, the discharge capacity is small and the cycle life characteristics are insufficient, so there is a need to improve the characteristics.
[0026] In addition, La2Ni 6.9-x Al 0.1 Fe x Although the (0≦x≦2.1) alloy itself is inexpensive, the only properties disclosed for the alloy are data on the gas-solid phase reactions related to hydrogen absorption and release. For this reason, the alloy disclosed in Non-Patent Document 6 exhibits insufficient properties as a hydrogen storage alloy for alkaline storage batteries. From this technical point of view, an inexpensive hydrogen storage alloy with favorable properties for battery use was needed.
[0027] Considering these technical points, to summarize from a technical standpoint, repeated hydrogen absorption and desorption causes cracks in rare earth-Mg-Ni based hydrogen storage alloys, accelerating pulverization and creating new surfaces. For this reason, if rare earth-Mg-Ni based hydrogen storage alloys have low corrosion resistance as alloys, their alloy surfaces will react to generate rare earth hydroxides, reducing the alloy portion with hydrogen absorption and desorption function. Furthermore, rare earth-Mg-Ni based hydrogen storage alloys with low corrosion resistance will consume the electrolyte that constitutes the battery, resulting in an increase in the battery's internal resistance and a decrease in discharge capacity, shortening the battery's life. On the other hand, in order to improve the hydrogen absorption ability of rare earth-Mg-Ni based hydrogen storage alloys, it is preferable for there to be a lot of Ni on the alloy surface, and the amount of Ni present on the alloy surface is determined by the balance of various battery characteristics.
[0028] The present invention has been made in consideration of these problems associated with the prior art, and has an object to provide a rare earth-Mg-Ni based alloy that is inexpensive, has extremely excellent cycle life characteristics, can be used in alkaline storage batteries with large discharge capacities, allows the amount of alloy to be reduced, and is also practical. [Means for solving the problem]
[0029] In order to achieve the above object, a hydrogen storage alloy having an A2B7 crystal structure and an A5B 19 By adopting a hydrogen storage alloy in which either one or both of the above crystal structures are the main phase and which contains Fe and Ce as essential compositional components, it has become possible to discover an alkaline storage battery which is low cost and has excellent cycle life characteristics, which has led to the development of the present invention.
[0030] The present invention is, first, a hydrogen storage alloy for use in an alkaline storage battery, the hydrogen storage alloy having an A2B7 type crystal structure and an A5B 19 The hydrogen storage alloy for alkaline storage batteries has a main phase having one or both of the following crystal structures and is represented by the following general formula (1): [ka] (In the general formula (1), M: at least one selected from Al, Zn, and Sn; T: at least one selected from Cr, Mo, V, Nb, and W; 0 <a≦0.10、 0≦b≦0.10, 0 <a+b≦0.18、 0.10≦c≦0.30, 0≦e≦0.14, 0≦f≦0.05, 0 <g≦0.35、 3.0≦d+e+f+g≦4.0 is satisfied.)
[0031] Secondly, the present invention relates to a compound represented by the general formula (1), in which M is Al and T is Cr, 0 <a+b≦0.15、 0.12≦c≦0.29, 0≦e≦0.12, 0 <g≦0.30、 A hydrogen storage alloy for alkaline storage batteries, characterized in that 3.30≦d+e+f+g≦3.80 is satisfied.
[0032] In addition, the hydrogen storage alloy for alkaline storage batteries is evaluated for its hydrogen absorption and desorption characteristics, PCT (Pressure-Composition-Temperature) characteristics. When using a hydrogen storage alloy for an alkaline storage battery, it is preferable that the hydrogen storage capacity, which is related to the discharge capacity of an alkaline storage battery, is 0.91 or more in H / M (H: number of hydrogen atoms, M: number of metal atoms) when a hydrogen pressure of 1 MPa is applied at a measurement temperature of 80°C. On the other hand, it was found that the gradient of the PCT characteristic, which is a hydrogen storage and desorption characteristic, near the hydrogen equilibrium pressure (hydrogen pressure when H / M=0.5) at the time of hydrogen desorption is particularly effective in the alloy of the present invention in terms of improving durability. Specifically, the hydrogen storage alloy for alkaline storage batteries according to the present invention is characterized in that, in the hydrogen storage and desorption characteristics, the hydrogen storage capacity (H / M) is 0.91 or more when a hydrogen pressure of 1 MPa is applied at a measurement temperature of 80°C, and the plateau gradient at the time of desorption after hydrogen absorption is in a range that satisfies the following relational expression (A).
number
[0033] The hydrogen storage alloy for alkaline storage batteries of the present invention reduces the cost of batteries, and alkaline storage batteries using this hydrogen storage alloy have high power density and excellent charge / discharge cycle life characteristics (durability), and therefore excellent discharge capacity characteristics. Therefore, the hydrogen storage alloy for alkaline storage batteries of the present invention can be used for various applications, particularly for alkaline storage batteries that can be discharged at a sufficiently high rate even under vehicle use conditions. [Brief description of the drawings]
[0034] [Figure 1] 1 is a partially cutaway perspective view illustrating an alkaline storage battery using the hydrogen storage alloy of the present invention. [Diagram 2]1 is an example of the PCT characteristic of the hydrogen storage alloy of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] Hereinafter, an embodiment of the present invention will be described. An alkaline storage battery using a hydrogen storage alloy according to this embodiment will be described with reference to Fig. 1, which is a partially cutaway perspective view showing an example of a battery. The alkaline storage battery 10 is a storage battery in which an electrode group consisting of a nickel positive electrode 1 having nickel hydroxide (Ni(OH)2) as a main positive electrode active material, a hydrogen storage alloy negative electrode 2 having a hydrogen storage alloy (MH) according to this embodiment as a negative electrode active material, and a separator 3 is provided in a housing 4 together with an electrolyte layer (not shown) filled with an alkaline electrolyte.
[0036] This alkaline storage battery 10 corresponds to a so-called nickel-metal hydride battery (Ni-MH battery), and the following reaction occurs inside the battery 10. [ka]
[0037] [Hydrogen storage alloy] The hydrogen storage alloy for alkaline storage batteries according to this embodiment will be described below. The hydrogen storage alloy for alkaline storage batteries according to this embodiment (hereinafter, simply referred to as "hydrogen storage alloy") is a hydrogen storage alloy used in alkaline storage batteries, and the hydrogen storage alloy has an A2B7 type crystal structure and an A5B 19 The present invention is characterized in that the main phase is one or both of the above-mentioned crystal structures and is represented by the following general formula (1). [ka] (In the general formula (1), M: at least one selected from Al, Zn, and Sn; T: at least one selected from Cr, Mo, V, Nb, and W; 0 <a≦0.10、 0≦b≦0.10, 0 <a+b≦0.18、 0.10≦c≦0.30, 0≦e≦0.14, 0≦f≦0.05, 0 <g≦0.35、 3.0≦d+e+f+g≦4.0 is satisfied.) Here, the A2B7 type crystal structure, A5B 19 The crystal structures of the Ce2Ni7 type and Gd2Co7 type, Pr5Co 19 Type and Ce5Co 19 It is a mold structure.
[0038] In addition, in the general formula (1), M is Al and T is Cr, 0 <a+b≦0.15、 0.12≦c≦0.29, 0≦e≦0.12, 0 <g≦0.30、 A hydrogen storage alloy for alkaline storage batteries that satisfies 3.30≦d+e+f+g≦3.80 can be a more preferable means for solving the problems.
[0039] In terms of hydrogen absorption and desorption characteristics, the hydrogen absorption capacity (H / M) is 0.91 or more when a hydrogen pressure of 1 MPa is applied at a measurement temperature of 80°C, and The hydrogen storage alloy for alkaline storage batteries is characterized in that the plateau slope during hydrogen release after absorption is within a range satisfying the following relational expression (A).
number
[0040] The reasons for limiting the composition of the hydrogen storage alloy of the present invention will be explained below. La, Ce, Sm:La 1-a-b Ce a Sm b(However, 0 < a ≤ 0.10, 0 ≤ b ≤ 0.10, 0 < a + b ≤ 0.18) The rare earth element constituting the hydrogen storage alloy of the present invention is La 1-a-b Ce a Sm b and is represented by 0 < a ≤ 0.10, 0 ≤ b ≤ 0.10, and the total of Ce and Sm does not include 0 and is 0.18 or less. That is, as elements constituting the A2B7-type crystal structure and the A5B 19 type crystal structure forming the main phase of the hydrogen storage alloy of the present invention, rare earth elements are contained. The rare earth element is composed of La, Ce, and Sm as basic components that bring hydrogen storage ability to the hydrogen storage alloy. La, Ce, and Sm each have a different atomic radius. Therefore, the hydrogen equilibrium pressure can be controlled by the component ratio of these rare earth elements constituting the hydrogen storage alloy, and the hydrogen equilibrium pressure required for the alkaline storage battery can be arbitrarily set. The component ratio (atomic ratio) of the rare earth element constituting the hydrogen storage alloy is such that Ce does not include 0 and is 0.10 or less, and Sm is 0 or more and 0.10 or less. That is, the hydrogen storage alloy of the present invention contains Ce as an essential compositional component. If it is within this range, it is easy to set the hydrogen equilibrium pressure suitable for the alkaline storage battery, and a hydrogen storage alloy having good corrosion resistance and difficulty in being pulverized can be obtained. As a result, high durability of the alkaline storage battery can be obtained. When each of Ce and Sm exceeds 0.10, the pulverization of the hydrogen storage alloy accompanying hydrogen storage and release progresses, and the durability of the alkaline storage battery gradually decreases. Also, the total of Ce and Sm does not include 0 and is 0.18 or less. If it is within this range, it is easy to set the hydrogen equilibrium pressure suitable for the alkaline storage battery, and it is also effective for improving the durability of the battery. Specifically, in the general formula (1), preferably, the atomic ratio a value of Ce in the rare earth element is in the range of more than 0 and 0.08 or less, and the atomic ratio b value of Sm is preferably in the range of 0 or more and 0.08 or less. On the other hand, the sum a + b value of the atomic ratios of Ce and Sm is preferably in the range of more than 0 and 0.15 or less.
[0041] A composition with a high La content is preferable because it increases the discharge capacity of an alkaline storage battery, and when combined with other elements, it further improves the discharge capacity characteristics of the alkaline storage battery and realizes low cost. In addition, expensive rare earth elements such as Pr, Nd, and heavy rare earth elements are not actively used, but they may be contained at the level of unavoidable impurities.
[0042] Mg:Mg c (where 0.10≦c≦0.30) Mg has the A2B7 type crystal structure, A5B 19 Mg is an essential element that constitutes the A component of the crystalline structure. Mg contributes to improving the discharge capacity of alkaline storage batteries by improving the reversibility of hydrogen absorption and release, and to improving cycle life characteristics. The c value, which represents the atomic ratio of Mg in the A component, is in the range of 0.10 to 0.30. If the c value is less than 0.10, the hydrogen release ability decreases, resulting in a decrease in the discharge capacity of the alkaline storage battery. On the other hand, if the value of c exceeds 0.30, cracking of the hydrogen storage alloy due to hydrogen absorption and release is accelerated, and the cycle life characteristics, i.e., durability of the alkaline storage battery is deteriorated. In the general formula (1), the value of c is preferably in the range of 0.12 or more and 0.29 or less.
[0043] Ni:Ni d Ni has the A2B7 type crystal structure, A5B 19 It is the main element of the B component of the crystalline structure. Its atomic ratio d value will be described later.
[0044] M:M e (where 0≦e≦0.14) M is at least one selected from Al, Zn, and Sn, and is mainly an A2B7 type crystal structure, A5B 19M is an element contained as the B component of hydrogen storage alloys having a crystalline structure. M is effective in adjusting the hydrogen equilibrium pressure related to the battery voltage of alkaline storage batteries, and can improve the corrosion resistance and durability of fine hydrogen storage alloys. In other words, M is effective in improving the cycle life characteristics of alkaline storage batteries. In order to ensure that the above-mentioned effects are exhibited, the value e, which represents the atomic ratio of M to the component A in the general formula (1), is set to be in the range of 0 or more and 0.14 or less. The effect of including Fe as a compositional component of the hydrogen storage alloy according to the present embodiment is that the cycle life characteristics of an alkaline storage battery having the hydrogen storage alloy as an electrode are improved, and therefore the M element contained in the hydrogen storage alloy can be reduced, thereby suppressing a decrease in the discharge capacity of the alkaline storage battery. If the e value exceeds 0.14, the discharge capacity of the alkaline storage battery decreases, and the hydrogen storage alloy is pulverized due to hydrogen storage and release, resulting in insufficient durability of the battery. The e value is preferably 0.12 or less. Among the M elements, Al is preferable.
[0045] T:T f (where 0≦f≦0.05) T is at least one selected from Cr, Mo, V, Nb, and W, and like M, it mainly has an A2B7 type crystal structure, A5B 19 It is an element contained as the B component in hydrogen storage alloys having a Cr-type crystal structure. T is effective in adjusting the hydrogen equilibrium pressure, which is related to the battery voltage of an alkaline storage battery, and can further improve the corrosion resistance of the hydrogen storage alloy through a synergistic effect with M, thereby improving the durability of the alkaline storage battery. T is particularly effective in improving the durability of fine hydrogen storage alloy particles, i.e., the cycle life characteristics of alkaline storage batteries. In order to ensure that the above-mentioned effects are exhibited, the value f, which represents the atomic ratio of T to the A component in the general formula (1), is set to be in the range of 0 or more and 0.05 or less. If the f value exceeds 0.05, the excess T element induces cracking of the hydrogen storage alloy due to the absorption and release of hydrogen, resulting in a decrease in durability and insufficient cycle life characteristics of the alkaline storage battery. The f value is preferably in the range of 0.002 to 0.04. Among the T elements, Cr is particularly preferable from the viewpoint of durability.
[0046] Fe:Fe g (However, 0 <g≦0.35) Fe has the A2B7 crystal structure and the A5B 19 The hydrogen storage alloy has one or both of the above crystal structures as a main phase, and is contained as component B. That is, Fe is an essential element of the hydrogen storage alloy according to the present invention. Fe is effective in adjusting the hydrogen equilibrium pressure, which is related to the battery voltage of an alkaline storage battery, and can also significantly improve the corrosion resistance and durability of the hydrogen storage alloy, i.e., is effective in improving the cycle life characteristics of the alkaline storage battery. By using Fe and Ce as essential constituent elements of the hydrogen storage alloy according to the present invention, the hydrogen equilibrium pressure can be easily controlled to a level suitable for alkaline storage batteries, and high corrosion resistance, high durability and low cost can be achieved. In order to ensure that the above-mentioned effects are truly achieved, the g value, which represents the atomic ratio of Fe in the general formula (1), is in the range of 0.35 or less, not including 0. If the g value exceeds 0.35, the discharge capacity decreases. The preferred g value is 0.01 or more and 0.30 or less. In the case of nickel-metal hydride batteries, due to restrictions on the battery capacity at the positive electrode, the hydrogen storage alloy used in the negative electrode is called a reservoir, and is 20 to 30 percent more than usual, in anticipation of alkaline corrosion of the hydrogen storage alloy by the alkaline solution used as the electrolyte. On the other hand, by employing the hydrogen storage alloy according to this embodiment, which contains Fe as an essential element, in an alkaline storage battery, the deterioration of the discharge capacity of the battery can be significantly suppressed. In other words, since the alkaline storage battery including the hydrogen storage alloy according to this embodiment is less susceptible to deterioration in discharge capacity, it is possible to significantly reduce the amount of hydrogen storage alloy used in this portion, which corresponds to the reservoir and is previously used in excess in anticipation of alkaline corrosion. In other words, in the hydrogen storage alloy according to this embodiment, by replacing part of the expensive Ni in the composition with inexpensive Fe, making Fe an essential element, it is possible to significantly reduce not only the material costs required to manufacture the hydrogen storage alloy, but also the amount of hydrogen storage alloy used in an alkaline storage battery. As a result, by employing the hydrogen storage alloy according to this embodiment, which contains inexpensive and easily available Fe as an essential element, in an alkaline storage battery, it is possible to reduce the manufacturing costs of the alkaline storage battery.
[0047] Ni, M, T and Fe:Ni d , M e , T f and Fe g (However, 3.0≦d+e+f+g≦4.0) Thus, the hydrogen storage alloy of the present invention has the A2B7 type crystal structure and the A5B 19 The A2B7 type crystal structure and the A5B type crystal structure contain Ni, M, T and Fe as elements constituting either one or both of them. 19 The stoichiometric ratio, which is the atomic ratio of component B (Ni, M, T and Fe) to component A of a hydrogen storage alloy having one or both of the above-mentioned crystal structures as the main phase, will be described below. That is, in the general formula (1), the value of d+e+f+g is preferably in the range of 3.0 to 4.0. If the value of d+e+f+g is less than 3.0, the subphase, i.e., the AB2 phase, increases, and the discharge capacity of the hydrogen storage alloy in particular decreases. On the other hand, if the value of d+e+f+g exceeds 4.0, the AB5 phase increases, and cracking of the hydrogen storage alloy due to hydrogen absorption and release is promoted, resulting in a decrease in the durability of the alkaline storage battery, i.e., the cycle life characteristics. The value of d+e+f+g is preferably in the range of 3.10 to 3.90, more preferably 3.30 to 3.80.
[0048] When applying a hydrogen storage alloy for battery applications, the hydrogen storage capacity and hydrogen equilibrium pressure are important in evaluating the hydrogen storage and release characteristics. Among these, the hydrogen storage capacity H / M (H / M; H is the number of hydrogen atoms, M is the number of metal atoms) is related to the discharge capacity of the battery, and it is preferable for the battery design that H / M is 0.91 or more when evaluated at 80°C and 1 MPa. If the hydrogen storage capacity H / M is less than 0.91, the battery will become larger, and in some cases, the amount of hydrogen storage alloy required per battery will increase. As a result, the cost required to manufacture a battery equipped with a hydrogen storage alloy will be high. From this perspective, the hydrogen storage capacity H / M is preferably 0.92 or more. The hydrogen storage capacity H / M is preferably 1.05 or less.
[0049] In addition, in order to improve the durability of alkaline storage batteries, i.e., to improve their cycle life characteristics, it is possible to suppress corrosion of new surfaces by improving the alkaline corrosion resistance of the surface of the hydrogen storage alloy and by suppressing pulverization of the hydrogen storage alloy that accompanies hydrogen absorption and release. The former is presumed to be due to the presence of Fe, which suppresses alkaline corrosion of the surface of the hydrogen storage alloy. On the other hand, with regard to the latter pulverization of hydrogen storage alloys, it was discovered that the gradient formed near the hydrogen equilibrium pressure (hydrogen pressure at H / M=0.5) at the time of release of the hydrogen absorption / desorption characteristics (PCT characteristics) in the PCT curve, which shows the relationship between the amount of hydrogen absorbed H / M and the hydrogen equilibrium pressure [MPa], is effective. In other words, when a hydrogen storage alloy absorbs hydrogen suddenly at a certain hydrogen pressure (the gradient is small), distortion occurs suddenly in the crystals of the alloy, accelerating cracking of the hydrogen storage alloy. On the other hand, if the hydrogen storage alloy slowly absorbs hydrogen at a constant hydrogen pressure (the gradient is large), the hydrogen pressure required to absorb a certain amount of hydrogen will increase. In other words, the battery reaction will not be able to fully charge the battery, and although the hydrogen storage alloy will be less likely to crack, the battery's discharge capacity will tend to decrease. Therefore, it is estimated that the durability will be significantly improved by the combined effect of the alkaline corrosion resistance of the hydrogen storage alloy surface and the suppression of cracking of the hydrogen storage alloy due to hydrogen absorption and release.
[0050] Specifically, the plateau slope when releasing hydrogen after absorption is calculated as [log(P0.7 / P0.3)] / 0.4 based on the hydrogen pressure (P0.3) when the hydrogen storage amount (H / M) is 0.3 and the hydrogen pressure (P0.7) when the hydrogen storage amount (H / M) is 0.7, and is 1.2 or more and 2.8 or less. If the plateau slope when releasing hydrogen after absorption is less than 1.2, the crystal lattice of the hydrogen storage alloy is likely to expand in one direction during hydrogen absorption, in other words, the crystal lattice of the hydrogen storage alloy is likely to expand and contract anisotropically, and it is presumed that the resulting strain promotes cracking of the hydrogen storage alloy. On the other hand, if the slope of the plateau when releasing hydrogen after absorption exceeds 2.8, the amount of hydrogen storage is difficult to increase even if hydrogen pressure is applied up to 1 MPa because the slope is large, and as a result, the amount of hydrogen storage decreases. From this viewpoint, the slope of the plateau when releasing hydrogen after absorption is preferably 1.3 to 2.7.
[0051] [Method of manufacturing hydrogen storage alloy] Next, a method for producing the hydrogen storage alloy according to this embodiment will be described. The hydrogen storage alloy according to this embodiment can be produced by a melting method. Specifically, the hydrogen storage alloy according to this embodiment is produced by weighing out rare earth elements (Sm, La, Ce, etc.) and metal elements such as magnesium (Mg), nickel (Ni), aluminum (Al), chromium (Cr), and iron (Fe) to a predetermined atomic ratio, and then putting these raw materials into an alumina crucible installed in a high-frequency induction furnace and melting them under an inert gas atmosphere such as argon gas, and then casting them into a mold to produce an ingot of the hydrogen storage alloy. The hydrogen storage alloy according to this embodiment can be manufactured by a strip casting method, and may be directly produced as a flake-shaped sample having a thickness of about 200 to 500 μm.
[0052] Since the hydrogen storage alloy according to this embodiment contains Mg, which has a low melting point and a high vapor pressure, as a main component, if all the raw materials of the alloy components constituting the hydrogen storage alloy are melted at once, the Mg alloy component will evaporate, and it may be difficult to obtain a hydrogen storage alloy with a target chemical composition. Therefore, when producing the hydrogen storage alloy according to this embodiment by a melting method, it is preferable to first go through a melting step in which the alloy components other than Mg are melted, and then to add Mg raw materials such as metallic Mg and Mg alloys into the molten metal. In addition, this dissolution step is desirably carried out in an atmosphere of an inert gas such as argon or helium, and specifically, it is preferably carried out in a reduced pressure atmosphere adjusted to 0.05 to 0.2 MPa with an inert gas containing 80 vol% or more of argon gas.
[0053] The hydrogen storage alloy melted under the above conditions is then preferably cast into a water-cooled mold and solidified to form an ingot of the hydrogen storage alloy. Next, the melting point (Tm) of each of the obtained hydrogen storage alloy ingots is measured using a DSC (differential scanning calorimeter). This is because the hydrogen storage alloy according to this embodiment is preferably subjected to a heat treatment in which the ingot after casting is held in an atmosphere of an inert gas such as argon or helium, or nitrogen gas, or a mixed gas thereof, at an appropriate temperature of 800°C or higher and lower than the melting point (Tm) of the hydrogen storage alloy for 3 to 50 hours. This heat treatment resulted in the formation of the A2B7 type crystal structure and the A5B type crystal structure as the main phase in the hydrogen storage alloy. 19 The total ratio of the A2B7 type crystal structure and the A5B type crystal structure is 70 mass% or more, preferably the A2B7 type crystal structure and the A5B 19 The total ratio of the AB2 phase and the AB5 phase, which are subphases formed during casting, can be reduced or eliminated by making the total ratio with the AB5 phase equal to or greater than 80 mass %. The crystal structure of the main phase of the obtained hydrogen storage alloy can be confirmed by X-ray diffraction measurement using Cu-Kα radiation.
[0054] If the heat treatment temperature is less than 800° C., the diffusion of the elements contained in the hydrogen storage alloy is insufficient, and subphases remain, which may result in a decrease in the discharge capacity and deterioration of the cycle life characteristics of an alkaline storage battery equipped with an electrode containing such a hydrogen storage alloy. On the other hand, if the heat treatment temperature is 20°C lower than the melting point (Tm) of the hydrogen storage alloy (Tm-20°C or higher), the crystal grains constituting the main phase of the hydrogen storage alloy may become coarse or partially melt, or the Mg component may evaporate, which may result in pulverization of the hydrogen storage alloy or a change in the chemical composition, resulting in a decrease in the amount of hydrogen storage. Therefore, the heat treatment temperature of the hydrogen storage alloy is preferably in the range of 800°C to (Tm-30°C).
[0055] Furthermore, if the heat treatment is held for 3 hours or less, the ratio of the main phase constituting the hydrogen storage alloy cannot be stably increased to 70 mass% or more, and the chemical composition of the main phase is not sufficiently homogenized, which may result in non-uniform expansion and contraction of the crystals constituting the hydrogen storage alloy during hydrogen absorption and release, increasing the amount of distortion and defects that occur in the hydrogen storage alloy and adversely affecting the cycle life characteristics of alkaline storage batteries. The holding time of the heat treatment is preferably 4 hours or more, and from the viewpoint of homogenizing the main phase of the hydrogen storage alloy and improving the crystallinity, it is more preferably 5 hours or more. However, if the heat treatment time exceeds 50 hours, the amount of evaporated Mg increases, causing a change in the chemical composition of the hydrogen storage alloy. As a result, the AB5 type subphase may be formed in the hydrogen storage alloy. Furthermore, this is not preferable because it increases the manufacturing cost of the hydrogen storage alloy and may cause a dust explosion due to evaporated Mg fine powder.
[0056] The heat-treated hydrogen storage alloy is pulverized into fine particles by a dry method or a wet method. When the hydrogen storage alloy is pulverized by a dry method, for example, a hammer mill or an ACM pulverizer can be used to pulverize the alloy, thereby obtaining a powder of fine particles of the hydrogen storage alloy having an average particle size of 20 to 100 μm. On the other hand, when the hydrogen storage alloy is pulverized by the wet method, it can be pulverized using a bead mill or an attritor. In particular, when obtaining fine powder consisting of hydrogen storage alloy particles with an average particle size of 20 μm or less, wet pulverization is preferable because it can safely produce hydrogen storage alloy particles. The particle size of the pulverized hydrogen storage alloy particles may be set to an appropriate range depending on the application, for example, the average particle size D50 may be set to 8 to 100 μm. Here, the average particle size D50 of the hydrogen storage alloy particles described above is a value measured by a laser diffraction / scattering type particle size distribution measuring device, as in the MV measurement, and the measuring device may be, for example, the MT3300EXII type manufactured by Microtrack Bell.
[0057] The hydrogen storage alloy according to this embodiment has a main phase with an A2B7 type crystal structure and an A5B 19 A hydrogen storage alloy with an A2B7 type crystal structure. Specifically, the A2B7 type crystal structure can have both the hexagonal (2H) Ce2Ni7 phase and the rhombohedral (3R) Gd2Co7 phase without any problem, and either one is acceptable. It is preferable for the A2B7 type crystal structure to contain a large amount of the former hexagonal (2H) Ce2Ni7 phase. Also, A5B 19 The crystal structure is hexagonal (2H) Gd5Co 19 phase and rhombohedral (3R) PrCo 19 The coexistence of both phases does not pose any problem, and either one may be used. A5B 19 The crystal structure of the former is hexagonal (2H) Gd5Co 19 It is preferable that the phase is contained in a larger amount. The main phase constituting the hydrogen storage alloy according to this embodiment is an A2B7 type crystal structure and an A5B 19 It is preferable that the total amount of the crystalline structure and the crystalline structure is at least 70 mass % or more. More preferably, the A2B7 crystal structure, A5B 19 The total amount of the phases of the type crystal structure is 80 mass % or more. The crystal structure of the main phase of these hydrogen storage alloys can be evaluated by Rietveld analysis based on the results of X-ray diffraction measurements.
[0058] The alloy particles obtained by pulverizing the hydrogen storage alloy according to this embodiment may then be subjected to a surface treatment such as an alkali treatment using an alkaline aqueous solution such as KOH or NaOH, or an acid treatment using an aqueous solution of nitric acid, sulfuric acid, or hydrochloric acid. By subjecting the alloy particles to such a surface treatment, a layer made of Ni (alkali-treated layer or acid-treated layer) is formed on at least a part of the surface of the alloy particles, which makes it possible to suppress the progress of corrosion of the hydrogen storage alloy and to increase its durability. As a result, the cycle life characteristics and discharge characteristics over a wide temperature range of an alkaline storage battery using the hydrogen storage alloy according to this embodiment can be improved. In particular, in the case of acid treatment of alloy particles, it is preferable to use hydrochloric acid because it is possible to precipitate Ni while minimizing damage to the alloy surface. In addition, when crushing the hydrogen storage alloy by a wet method, the surface treatment can be performed at the same time. EXAMPLES
[0059] The present invention will be described below with reference to examples. <Example 1> Evaluation cells using hydrogen storage alloys No. 1 to 48 (hereinafter, simply referred to as "alloys") having the composition shown in Tables 1-1 to 1-3 below as negative electrode active materials were prepared as described below, and experiments were conducted to evaluate the characteristics of the evaluation cells. Alloys No. 1 to 31 shown in Tables 1-1 and 1-2 are alloy examples (invention examples) that meet the conditions of the present invention, and No. 32 to 48 shown in Tables 1-2 and 1-3 are alloy examples (comparative examples) that do not meet the conditions of the present invention. Furthermore, alloy No. 32 of the comparative example was used as a reference alloy for evaluating the characteristics of the evaluation cells.
[0060] (Preparation of negative electrode active material) The raw materials of alloys No. 1 to 48 shown in Tables 1-1 to 1-3 (Sm, La, Ce, Mg, Ni, Al, Cr, and others, each with a purity of 99% or more) were melted in an argon atmosphere (Ar: 100 vol%, 0.1 MPa) using a high-frequency induction heating furnace and cast into alloy ingots. Next, these alloy ingots were heated in an argon atmosphere (Ar: 90 vol%, 0.1 MPa) until the melting point T m After heat treatment at -50°C (940 to 1130°C) for 10 hours, the material was coarsely crushed and then finely crushed in a hammer mill to a mass-based D50 of 25 μm to obtain an evaluation sample (negative electrode active material) for the evaluation cell. In addition, the alloys No. 1 to No. 31 of the invention examples of the present invention were subjected to X-ray diffraction measurement of the powders crushed after heat treatment, and it was found that the main phases in all of them were A2B7 phase and A5B 19 It has been confirmed that the crystal structure is composed of at least one selected from the above phases.
[0061] (Preparation of evaluation cells) <Negative electrode> The negative electrode active material prepared above, Ni powder as a conductive additive, and two types of binders (styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC)) were mixed in a weight ratio of negative electrode active material:Ni powder:SBR:CMC=95.5:3.0:1.0:0.5, and kneaded to form a paste-like composition. This paste-like composition was applied to a punching metal, dried at 80℃, and then roll-pressed with a load of 15kN to obtain a negative electrode.
[0062] <Positive electrode> Nickel hydroxide (Ni(OH)2), metallic cobalt (Co) as a conductive additive, and two types of binders (styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC)) were mixed in a mass ratio of Ni(OH)2:Co:SBR:CMC=95.5:2.0:2.0:0.5 and kneaded to form a paste-like composition. This paste-like composition was applied to porous nickel, dried at 80℃, and then roll-pressed with a load of 15kN to obtain a positive electrode.
[0063] <Electrolyte> The electrolyte used was an alkaline aqueous solution prepared by mixing potassium hydroxide (KOH) in pure water to a concentration of 6 mol / L.
[0064] <Evaluation cell> The positive electrode and the negative electrode were placed in an acrylic case as a counter electrode and a working electrode, respectively, and the electrolyte was poured into the cell to prepare a cell using a Hg / HgO electrode as a reference electrode, and the cell was subjected to an evaluation test. At this time, the capacity ratio of the working electrode and the counter electrode was adjusted to be working electrode:counter electrode=1:3.
[0065] (Cell Characterization) The evaluation tests of the evaluation cells for the alloys Nos. 1 to 48 obtained as described above were carried out as follows. The evaluation temperature was 25° C. for all the tests.
[0066] (1) Discharge capacity of the electrode The discharge capacity of the working electrode was confirmed using the following procedure. After constant current charging at a current value of 80 mA / g per active material of the working electrode for 10 hours, constant current discharging was performed at a current value of 40 mA / g per active material of the working electrode. The discharge termination condition was a working electrode potential of -0.5 V. The above charge / discharge was repeated five times, and the maximum value of the discharge capacity was taken as the discharge capacity of the working electrode. It was confirmed that the discharge capacity of the working electrode was saturated and stabilized after 10 charge / discharge cycles. The measured discharge capacity was calculated by the following relational formula (2) with the discharge capacity of Alloy No. 32 shown in Table 1-2 taken as the reference capacity.
number
[0067] (2) Cycle life characteristics Using the cells in which the discharge capacity of the working electrode was confirmed in the above (1) Discharge capacity of electrode, the cycle life characteristics of the working electrode were determined by the following procedure. When the current value required to complete charging or discharging the discharge capacity of the working electrode confirmed in (1) Discharge capacity of electrode in 1 hour was defined as 1C, constant current charging and constant current discharging were performed at a current value of C / 2 within a range of 20-80% charge rate of the working electrode, and this cycle was repeated 200 times. The discharge capacity after 200 cycles was measured, and the capacity retention rate was calculated using the following relational formula (3).
number
number
[0068] (3) PCT characteristics and plateau gradient evaluation of negative electrode active material The hydrogen absorption and desorption characteristics of each alloy obtained were evaluated using a PCT (Pressure-Composition-Temperature) device. The alloys used for evaluation were alloy particles with a particle size ranging from 150 μm to 2 mm, and the measurement temperature was 80°C. Once, hydrogen pressure was applied up to 3 MPa as an activation treatment, and after the absorbed hydrogen was released, hydrogen pressure was applied stepwise up to over 1 MPa, and then the pressure was reduced and measured. The hydrogen absorption amount was determined as H / M (H: hydrogen, M: metal) when 1 MPa was applied. In addition, the plateau gradient was calculated using the relational equation [log(P0.7 / P0.3)] / 0.4 by measuring the hydrogen pressures at H / M=0.7 and H / M=0.3 on the hydrogen release curve. As an example, Fig. 2 shows the PCT curve of alloy No. 1 of the present invention. The hydrogen equilibrium pressure of this alloy is 0.036 MPa according to the above definition. The plateau gradient was 1.67. In alloy No. 1 of the present invention, this plateau gradient value, together with the effect of Fe substitution, has a significant effect on the cycle life characteristics of an alkaline storage battery.
[0069] (4) Cost The alloy cost (material cost of the alloy) was calculated from the unit price per mass and mass ratio of each raw material of the alloy with the composition shown in Tables 1-1 to 1-3. It was then evaluated relative to the standard alloy No. 32. The cost evaluation shown in Tables 1-1 to 1-3 was as follows: alloys 0.95 or less than the standard alloy were rated as ◎, alloys between 0.95 and 1.0 were rated as ○, alloys between 1.0 and less than 1.05 were rated as △, and alloys 1.05 or more were rated as ×.
[0070] Tables 1-1 to 1-3 summarize the evaluation results of the above characteristics. As is clear from these tables, the alloys of the invention examples No. 1 to 31 have improved values of discharge capacity and cycle life characteristics compared to the comparative example (reference example) No. 32, and the improvement in cycle life characteristics is particularly remarkable. At the same time, low cost can be achieved. In contrast, the alloys of the comparative examples No. 32 to 48 clearly show a significant difference, especially in cycle life characteristics, or are expensive alloys.
[0071] [Table 1-1]
[0072] [Table 1-2]
[0073] [Table 1-3] [Industrial Applicability]
[0074] An alkaline storage battery comprising the hydrogen storage alloy for alkaline storage batteries of the present invention is superior in both discharge capacity and cycle life characteristics to alkaline storage batteries comprising the conventionally used AB5-type hydrogen storage alloy. Furthermore, the battery can be manufactured at low cost. Therefore, the hydrogen storage alloy for alkaline storage batteries of the present invention is suitable as an alloy for the negative electrode of a wide range of alkaline storage batteries, from consumer applications as a replacement for alkaline primary batteries to various industrial applications and vehicle applications, and is extremely useful industrially. [Explanation of symbols]
[0075] 1: Positive electrode 2: Negative electrode 3: Separator 4: Housing (battery case) 10: Alkaline storage battery
Claims
1. A hydrogen storage alloy for use in an alkaline storage battery, the hydrogen storage alloy being A 2 B 7 Type crystal structure and A 5 B 19 1. A hydrogen storage alloy for an alkaline storage battery, comprising one or both of the following crystal structures as a main phase, and represented by the following general formula (1): 【Chemistry 1】 (In the general formula (1), M: at least one selected from Al, Zn, and Sn; T: at least one selected from Cr, Mo, V, Nb, and W; 0<a≦0.10, 0≦b≦0.10, 0<a+b≦0.18, 0.10≦c≦0.30, 0≦e≦0.14, 0≦f≦0.05, 0<g≦0.35, 3.0≦d+e+f+g≦4.0 is satisfied.)
2. In the general formula (1), M is Al and T is Cr, 0<a+b≦0.15, 0.12≦c≦0.29, 0≦e≦0.12, 0<g≦0.30, 2. The hydrogen storage alloy for an alkaline storage battery according to claim 1, wherein 3.30≦d+e+f+g≦3.80 is satisfied.
3. In terms of hydrogen absorption / release characteristics, the hydrogen absorption capacity (H / M) when a hydrogen pressure of 1 MPa is applied at a measurement temperature of 80° C. is 0.91 or more, and 3. The hydrogen storage alloy for an alkaline storage battery according to claim 1, wherein a plateau slope at the time of releasing hydrogen after absorption is within a range satisfying the following relational expression (A): [0010] (Here, in the relation (A), P0.7 is the hydrogen pressure [MPa] when the hydrogen storage capacity (H / M) is 0.7, P0.3 represents the hydrogen pressure [MPa] when the hydrogen storage capacity (H / M) is 0.3.
Citation Information
Patent Citations
Rare earth nickel magnesium intermediate alloy for hydrogen storage alloy and preparation method of rare earth nickel magnesium intermediate alloy
CN102534326A
Hydrogen storage electrode alloy for Ni-MH battery and preparation method thereof
CN103682288A
Metal materials for hydrogen storage
JP1977070916A
Hydrogen storage alloy and secondary battery
JP1999323469A
Nickel material for battery, negative electrode, and battery case material
JP2019016587A
Cited By
A2B7 type Y-Mg-Ni series hydrogen storage material and preparation method thereof
CN120311074A